The Kuda Pattu’duq Tradition in the Perspective of Maqashid Al-Shari’ah - Hasanuddin, Hasriah; Hasan, Hamzah; Ilyas, Musyfikah (Hikmah, 2026)
This study examines the role of the kuda pattu’duq tradition in the community of Campalagian District, Polewali Mandar Regency, from the perspective of maqashid al-shari’ah. The research focuses on how this tradition conveys social and religious meaning and its impact on community life. The objectives are to identify the significance of kuda pattu’duq, explore its relevance to maqashid al-shari’ah principles, and analyze its implications for social and religious life. A qualitative approach was employed, combining phenomenological, sociological, and sharia perspectives. Data were collected through observation, interviews, and documentation from cultural figures, community leaders, youth, religious leaders, and government officials, then analyzed thematically. Findings indicate that horses, riders, traditional attire, kalindaqdaq, and rebana hold symbolic social and religious meanings; maqashid al-shari’ah emphasizes the protection of religion (hifdz ad-din), life (hifdz an-nafs), and wealth (hifdz al-maal) as guiding principles for the tradition; while its social and religious implications include enhanced solidarity, cultural promotion, motivation for Qur’an recitation, and parental expressions of gratitude. This study demonstrates that the kuda pattu’duq tradition strengthens Mandar cultural identity while fostering religious understanding among the younger generation.